Antigenic Relationships of Alphaviruses by a Simple Micro-culture Cross-neutralization Method - Chanas, A. C.; Johnson, B. K.; Simpson, D. I. H. (Journal of General Virology, 1976)
SUMMARY A cross-neutralization study of 22 alphaviruses disclosed two major antigenic complexes and two viruses that were distinct from all the others. Cross-reactions were common but were restricted within the complexes. Sub-groupings within a complex were also shown, and some viruses proved to be indistinguishable by neutralization testing. The results generally paralleled previously reported data. Investigations were carried out, using BHK 21 cells in a micro tissue-culture system, on all available alphaviruses.